Effect of Uncaria Tomentosa leaves extract on Histopathological changes in Murine Model of Asthma - Gulpash Saghir, Muhammad Sair, Iram Kamal, Sophia Abbasi, Faiza Khan, Faiza Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bronchial asthma is the leading respiratory disease among all chronic inflammatory conditions. Due to various causative factors, it’s incidence has been drastically increased over last decades. Despite the availability of potent anti inflammatory & bronchodilator therapies, there is a need to find new pharmacological molecules possessing targeted mechanism and lesser side effects towards it’s pathogenesis. In this study, Uncaria tomentosa belonging to family Rubiacae was selected to evaluate anti asthmatic effect owing to it’s specific anti inflammatory properties. Aim: To evaluate the effectiveness of uncaria tomentosa leaves on respiratory smooth muscles in case of bronchospasm and constriction. Study Design: Experimental comparative type Place and Duration of Research: University of health sciences. Duration of study is 1 year Methodology: Ethanolic extract of Uncaria tomentosa leaves was prepared according to the protocol. We took 24 male mice and divided them equally in groups of four. These groups represented control, diseased, UT (Uncaria tomentosa) leaves and MP (Methylprednisolone) treated. Bronchial asthma was induced by Ova sensitization on day 0 and OVA challenge on day 14 followed by treatment with UT leaves extract (200µg/animal/day) and MP (15mg/kg b.w) for next 7 days. Animals were sacrificed and lungs were removed to check histopathological findings. Results: The animals belonging to diseased group showed all histopathological features suggestive of bronchial asthma as compared to control group. Inflammatory score, epithelial cell hyperplasia and vascular congestion was found to be significantly decreased in both treatment groups. Conclusion: UT leave extract may possess anti asthmatic activity comparable to Methylprednisolone. Keywords: Phosphate Buffer Saline PBS, Tumor necrosis factor alpha TNF-α, Methylprednisolone MP, Uncaria tomentosa UT